2007
DOI: 10.1291/hypres.30.797
|View full text |Cite
|
Sign up to set email alerts
|

Renal-Protective Effect of T- and L-Type Calcium Channel Blockers in Hypertensive Patients: An Amlodipine-to-Benidipine Changeover (ABC) Study

Abstract: Both strict blood pressure control and efferent artery dilatation are critical in reducing proteinuria, which in turn helps to regulate blood pressure. Benidipine, an L-and T-type calcium channel blocker, has the potential for increased effectiveness compared with L-type-dominant calcium channel blockers such as amlodipine. Therefore, we evaluated blood pressure and proteinuria after changeover from amlodipine to benidipine in poorly controlled hypertensive patients. Fifty-eight hypertensive outpatients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
4
36
0
1
Order By: Relevance
“…16 -18 In a changeover study, benidipine (L-and T-type antagonist) caused a larger reduction in blood pressure and proteinuria compared with L-type treatment using amlodipine. 16 The observation of superior renoprotective effects with a combined L-and T-type treatment is in agreement with demonstration of a vasoconstrictor effect of T-type channels on efferent arterioles in animal studies.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…16 -18 In a changeover study, benidipine (L-and T-type antagonist) caused a larger reduction in blood pressure and proteinuria compared with L-type treatment using amlodipine. 16 The observation of superior renoprotective effects with a combined L-and T-type treatment is in agreement with demonstration of a vasoconstrictor effect of T-type channels on efferent arterioles in animal studies.…”
supporting
confidence: 83%
“…16 -18 In a crossover study, benidipine (L-and T-type antagonist) caused a larger reduction in blood pressure and proteinuria compared with L-type treatment using amlodipine, 16 and benidipine favorably affects renal function in patients with essential hypertension compared with amlodipine. 18 These studies suggest a clinical benefit of benidipine over amlodipine as an antihypertensive drug because of a renoprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was reported that a higher urinary protein excretion (Po0.0001), lower GFR (P¼0.0011) and the presence of diabetes (P¼0.0284) correlated with the reduction of urinary proteins when the treatment with amlodipine was replaced with treatment with benidipine. 13 The difference between our study and the CARTER study could be attributed to the large number of diabetic nephropathy cases included in our study. Moreover, the baseline proteinuria and sCr levels reflected a greater deterioration in patients in our study than in those of the CARTER study.…”
Section: Discussionmentioning
confidence: 60%
“…In renal tissues, the L-type calcium channels are present only in the afferent arterioles, whereas the N-type and T-type calcium channels are localized in both efferent and afferent arterioles. 12,13 Amlodipine is a representative CCB that is used widely all over the world; it blocks the L-type calcium channel and dilates the afferent arterioles to a higher degree than the efferent arterioles. 14,15 However, it has recently been reported that both a dual L-/N-type CCB cilnidipine and an L-/T-type CCB efonidipine exhibit a greater antiproteinuric effect than does amlodipine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation